Genetic Determinants of Complicated Pregnancy - Reshetnikov, Evgeny A. (Asian Journal of Pharmaceutics (AJP), 2019)
Objectives: The connections of polymorphic variants of the gene of vasoactive hormones with the level of arterial pressure in pregnant women, depending on the development of preeclampsia (PE), have been studied. Materials and Methods: The study group included 382 pregnant women diagnosed with PE and 205 women with normal pregnancy. Polymorphisms of the endothelin-1 gene rs5370 (G>T EDN1) and guanine-binding protein β3 subunit gene rs2301339 (G>A GNB3) were studied by real-time polymerase chain reaction (PCR) of DNA synthesis (real-time PCR). Results: Women with PE with genotype TT EDN1 have lower values of systolic, diastolic, and mean arterial pressure at the end of pregnancy compared to those with G EDN1 allele (genotypes GG and GT, P = 0.01–0.04). Conclusions: Thus, as a result of this study, significant associations of genetic polymorphisms with blood pressure indicators in pregnant women with PE were established.